Intraoperative dexmedetomidine attenuates postoperative systemic inflammatory response syndrome in patients who underwent percutaneous nephrolithotomy: a retrospective cohort study - Tan F; Gan X; Deng Y; Li X; Guo N; Hei Z; Zhu Q; Chen ZG; Zhou S (Dove Medical Press, 2018)
Fang Tan,1,2,* Xiaoliang Gan,3,* Yingqing Deng,1 Xiaoyun Li,1 Na Guo,1 Ziqing Hei,1 Qianqian Zhu,1 Zhuang-Gui Chen,4 Shaoli Zhou1 1Department of Anesthesiology, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou, People’s Republic of China; 2Department of Anesthesiology, The Seventh Affiliated Hospital of Sun Yat-sen University, Shenzhen, People’s Republic of China; 3Department of Anesthesiology, Zhongshan Ophthalmic Center of Sun Yat-sen University, Guangzhou, People’s Republic of China; 4Department of Pediatric Intensive Care Unit, Department of Pediatrics, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou, People’s Republic of China *These authors contributed equally to this work Purpose: Dexmedetomidine (DEX) has been reported to attenuate inflammation in rats. The present retrospective cohort study aimed to investigate whether intraoperative administration with DEX could reduce the incidence of postoperative systemic inflammatory response syndrome (SIRS) in patients following percutaneous nephrolithotomy (PCNL). Patients and methods: A total of 251 patients were included in the analysis. Among these patients, 175 received intravenous DEX infusion during the intraoperative period and 76 did not. The primary outcome measures were the incidences of postoperative SIRS and fever. Secondary outcomes included patient-controlled analgesia (tramadol) requirements, length of postoperative hospitalization stay, serum creatinine (Scr) and serum blood urea nitrogen (BUN) concentration, and adverse events (bradycardia, hypotension, renal artery thrombosis). Results: Administration of DEX not only significantly attenuated the incidence of SIRS and fever (P=0.029, P=0.042, respectively), but also reduced analgesia requirements (P=0.028). The length of postoperative hospitalization stay, Scr and BUN concentration, and adverse events did not differ significantly between the two groups. Further univariate and multivariate logistic regression analysis indicated that intraoperative DEX administration was a protective factor against SIRS after PCNL (OR 0.476 [95% CI: 0.257–0.835]; P=0.019). Conclusion: Intraoperative administration of DEX might be associated with reductions in the incidences of SIRS and fever after PCNL. Keywords: PCNL, SIRS, risk factor, dexmedetomidine